Robust Protective Effect of COVID-19 Vaccination in India—Results of Survey in the Midst of Pandemic’s Second Wave - Parikh, Purvish M.; Maheshwari, Udip; Krishna, V. M.; Gupta, S.; Patil, T.; Mandhaniya, S.; Mehta, P.; Somashekhar, S. P.; Parekh, B.; Singh, R. (South Asian Journal of Cancer, 2021)
Introduction Our objective was to document the incidence of COVID-19 in vaccinated health care professionals and related personnel.Method We conducted an online survey to ascertain the incidence of COVID-19 symptoms, reverse transcriptase polymerase chain reaction (RT-PCR) positivity, effect on normal activity, need for anti-COVID-19 medication, hospitalization, and death among individuals who had completed both doses of COVID vaccination at least 2 weeks earlier.Results A total of 351 unique valid responses were received. Among the 340 people who had been vaccinated in India, 5% (17/340) had COVID-19 symptoms, 4.7% (16) became COVID-19 RT-PCR positive, 12 (3.5%) had sickness preventing normal daily activity, 2.65% (9) required anti-COVID-19 medication, and 1.18% (4) required hospitalization. Among family members living with the survey responders, the corresponding incidence was even lower. There was one death in this group.Discussion Being health care professionals, the responders would be at higher risk of daily exposure to COVID-19. Even in this high risk group, the vaccine efficacy is good. Vulture journalists should stop spreading fake news and misinformation that makes people hesitate taking the vaccine or be afflicted analysis paralysis. Every person who chooses to remain unvaccinated increases the risk for our entire community. We also need to follow universal precautions (wearing mask, physical distancing, handwashing) diligently without letting down our guard.
Keywords: covishield; covaxin; clinical benefit; preventing death; preventing hospitalization; Buridean’s ass; analysis paralysis; vulture journalism; inflammatory fake news